Back Cover: Exonuclease and Nicking Endonuclease‐Assisted Amplified Electrochemical Detection of Coralyne (ChemElectroChem 8/2017). Issue 8 (28th June 2017) - Wang, Jue; Yu, Jing; Zhou, Xiaoyu; Miao, Peng
Abstract : The Back Cover picture illustrates the principle of the exonuclease and nicking endonuclease‐based detection of coralyne on a DNA‐tetrahedron‐modified electrode. More information can be found in the Communication by J. Wang et al. onpage 1828 in Issue 8, 2017 (DOI:10.1002/celc.201700400 ).